Efficient isolation and culture of endothelial cells from venous malformation using the Rho-associated protein kinase inhibitor Y27632. Issue 1 (2nd January 2018) - Satoh, Takashi; Kurita, Masakazu; Suga, Hirotaka; Eto, Hitomi; Ozaki, Mine; Takushima, Akihiko; Harii, Kiyonori
Abstract: Background: The investigation of primary cells from a pathological lesion can elucidate the pathogenesis of diseases, but, for vascular malformations in humans, such basic research is still stagnant, because the isolation and culture of vascular endothelial cells (ECs) is very difficult. To obtain a sufficient amount of ECs from venous malformation (VM) this study took advantage of a Rho-associated protein kinase inhibitor, Y27632, which had been used for the efficient procurement of primary keratinocytes. Methods: ECs were isolated and cultured from VM lesions, combining enzymatic digestion, cell sorting, and Y27632. The proliferative effect of Y27632 on ECs was examined by proliferation assay. The characteristics of the ECs cultured with Y27632 by EC marker expression and tube formation assay were also examined. Results: Y27632 enhanced the proliferation of ECs and elongated the senescence of the cells. The expression of specific markers of ECs such as von Willebrand factor, endothelin-1, and VE-cadherin, was confirmed in the cells cultured with Y27632. In a tube formation assay, the cells cultured with Y27632 showed higher tube formation ability compared to the cells cultured without Y27632, indicating that Y27632 promoted the angiogenic capability of ECs. Conclusions: The protocol using Y27632 offers a new EC culture methodology and provides a new option for the biological investigation of vascular malformations. This new method will contribute to other types of vascular biology research as well.